Systematic review of the effectiveness of selected drugs for preventive chemotherapy for Taenia solium taeniasis - Haby, Michelle M.; Sosa Leon, Leopoldo A.; Luciañez, Ana; Nicholls, Ruben Santiago; Reveiz, Ludovic; Donadeu, Meritxell (PLOS Neglected Tropical Diseases, 2020)
Author summary Taeniasis and cysticercosis caused by Taenia solium are considered, by the WHO, to be neglected tropical diseases. Preventive chemotherapy for taeniasis in endemic populations is a useful tool for control of the parasite. Preventive chemotherapy can be implemented by treating the whole population in endemic areas at regular intervals (known as mass drug administration). While different drugs, doses and regimes have been used there were still uncertainties about which drugs and dose have the best efficacy while considering adverse effects. We conducted a systematic review of the best available literature to inform a WHO guideline for preventive chemotherapy. We found that praziquantel 10mg/kg, niclosamide 2g, and triple dose albendazole 400mg (400mg per day for three consecutive days) are all effective. Proven side-effects were mild and short-lived, when they did occur.